If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18x + 4y = 74 Solving -18x + 4y = 74 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -18x + 4y + -4y = 74 + -4y Combine like terms: 4y + -4y = 0 -18x + 0 = 74 + -4y -18x = 74 + -4y Divide each side by '-18'. x = -4.111111111 + 0.2222222222y Simplifying x = -4.111111111 + 0.2222222222y
| X+x-3+x+5=35 | | x(x^2-25)=0 | | 5(x-6)+6=7x-6 | | X+(x+5)+(x-3)=35 | | x(x+5)(x-1)=0 | | 6-6x=5x-8x+15 | | x^2+y^2+z=1 | | 5(6y-4)+19=3(4y+4)+7 | | 3(2y-4)+18=4(3y+1)+1 | | x^2+y^2-z=1 | | 7x-3=2x-5 | | 14x-20-13x=-14 | | 6x+7x-76=95-6x | | 105=(p^2-p) | | -18x-13=15x-4 | | x^2-37x-120=0 | | s=(p^2-p) | | 8x+4=4x+6 | | 9(x+4)+2=-9(x-8)-6 | | 7x+3=6(x+8)-8 | | 8c^2-24c+16=0 | | x+5x=-48 | | (x+3)(x+3)=-4x-15 | | p^2-64=0 | | 5.2x=29.64 | | -4x+1=21 | | p^2+1p=0 | | 2z(3z-1)=9z-3 | | p(p-16)=-48 | | x^2=1x+90 | | 2x-0.1=6.6x-37.82 | | -6y+4(6y-6)=-5+7(1-y) |